The Poverty of the Global Order - Da Costa, Dia; Mcmichael, Philip (Globalizations, 2007)
This paper argues that the legitimacy of the global order depends not on economic progress alone, but on the progressive naturalization of its epistemological foundations, through 'new solutions' to old problems by states and development agencies. New solutions become methods of social control through which the dominant visions of what count as viable futures are reproduced. We critique efforts to humanize development (e.g., by the World Bank, Amartya Sen) as evidence of development's epistemological crisis. Deploying Karl Polanyi's distinction between formal and substantive economy, we consider examples of substantive economy, which realize equality through strategic sovereignty and representational power, in collective and individual terms. These represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects development studies and international relations. Este documento sostiene que la legitimidad del orden global no depende solamente del progreso económico, sino de la naturalización progresiva de sus fundamentos epistemológicos, a través de 'nuevas soluciones' a problemas antiguos mediante estados y agencias del desarrollo. Las nuevas soluciones se convierten en métodos de control social, a través de los cuales se reproducen las visiones dominantes de lo que cuenta como futuros viables. Criticamos los esfuerzos de humanizar al desarrollo (p.e. Banco Mundial, Amartya Sen) como evidencia de la crisis del desarrollo epistemológico. Utilizando la distinción de Kart Polanyi entre economía formal y economía sustancial, consideramos ejemplos de una economía sustancial, la cual realiza la igualdad por medio de una soberanía estratégica y un poder representativo, en términos colectivos e individuales. Estas, entre otras iniciativas, representan 'espacios de esperanza' prácticos y epistemológicos para criticar la crisis de la epistemología de mercado que infecta a los estudios de desarrollo y las relaciones internacionales.
Developent Studies; Sociology
Keywords: formal economy; international law; international relations; international trade; social control; social epistemology; sovereignty; substantive economy

The making of US monetary policy: Central bank transparency and the neoliberal dilemma - Krippner, Greta (Theory & Society, 2007)
This article explores the implications of the Federal Reserve’s shift to transparency for recent debates about neoliberalism and neoliberal policymaking. I argue that the evolution of US monetary policy represents a specific instance of what I term the “neoliberal dilemma.” In the context of generally deteriorating economic conditions, policymakers are anxious to escape responsibility for economic outcomes, and yet markets require regulation to function in capitalist economies (Polanyi ). How policymakers negotiate these contradictory imperatives involves a continual process of institutional innovation in which functions are transferred to markets, but under the close control of the state. Thus, under transparency, Federal Reserve officials discovered innovations in the policy process that enabled “markets to do the Fed’s work for it.” These innovations enlisted market mechanisms, but did not represent a retreat from the state’s active role in managing the economy.
Sociology
Keywords: Board of Governors of the Federal Reserve System (U.S.); United States; capitalists & financiers; monetary policy; neoliberalism; policy sciences; public spending

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Political Science; Sociology
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

The Future of Sociology - Burawoy, Michael (Sociological Bulletin, 2007)
Like a hurricane, third-wave marketisation is picking up velocity and destroying societies in its path, destroying the very grounds upon which sociology grows. Sociology and humanity have a common interest in upholding civil society, and keeping state and market at bay. Working with Karl Polanyi's The Great Transformation, I diagnose three waves of marketisation associated with the commodification of labour, money and land, generating counter-movements at local, national and global levels. I argue that sociology is reshaped with each wave: in the first, it is utopian; in the second, it is driven by policy concerns; whereas emerging with the third wave marketisation is public sociology. The possibilities and challenges of public sociology as well as its relation to policy, critical and professional sociology are the subjects of this paper.
Sociology
Keywords: commodification; countermovement; government policy; humanity; labor; marketisation; markets; nature; public sociology; social sciences; societies; sociology; utopian socialism

The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Political Science; Sociology
Keywords: Athens (Greece); FINLEY; M. I. (Moses Israel); 1912-1986; Greeks; WEBER; Max; 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics

Public sociology vs. the market - Burawoy, Michael (Socio-Economic Review, 2007)
Building on Karl Polanyi's theory of a societal reaction to the unregulated exchange of what he called fictitious commodities—labour, money and land—this paper links the history of sociology to the history of the market. If the first wave of marketization in the nineteenth century dwelt on the commodification of labour, prompting utopian sociologies, and the second wave of marketization of the twentieth century was provoked by the commodification of money, generating national policy sociologies, then the third wave of marketization that began in the last quarter of the twentieth century includes the commodification of the environment (land, air, water), and calls for public sociologies of a global dimension.
Sociology
Keywords: commercial products; fictitious commodities; government policy; history of sociology; markets - social aspects; publicity - social aspects; social theory; socioeconomics; utopian socialism

Understanding the Diverging Trajectories of the United States and Western Europe: A Neo-Polanyian Analysis - Block, Fred (Politics & Society, 2007)
This article proposes a neo-Polanyian theoretical framework for understanding the dynamics within contemporary market societies. It uses this framework to analyze the divergence between the United States and other developed societies that has become more pronounced in the first years of the twenty-first century. The argument emphasizes the shifting political alliances of the business community in the United States and suggests that from 1994 onward, business lost power in the right-wing coalition to its religious Right allies. The growing power of a religious-based social movement is a critical ingredient in the unilateralist turn in the Bush Administration’s foreign policy.
Sociology
Keywords: U.S. business; economic sociology; embedded economy; embeddedness; social theory; varieties of capitalism

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Sociology
Keywords: economic history; economic sociology; embeddedness; political economy

Embeddedness, Path Dependency and Social Institutions: An Economic Sociology Approach - Ghezzi, Simone; Mingione, Enzo (Current Sociology, 2007)
This paper argues for a theoretical approach based on embeddedness which assumes that the economic actor is not an atomized and utilitarian individual, but is in fact positioned within specific historical and institutional contexts in various social networks. This approach is based on Polanyi's critically debated contribution which allows for an empirical study of the diversity of institutional structures and of the significance of configurations of insertion within different social networks. Such diversity results from the double movement of disembeddedness and re-embeddedness caused by the spread of constantly emerging market opportunities, and by the importance held by the historically and culturally different selective processes of path dependency in the construction of the institutions of social regulation and of the socialized preferences of economic actors. Within these processes attention is given to the transformation of social systems based on reciprocity (household, kin, social capital networks, etc.), associations of shared interests, forms of economic organization (in a plurality of coexisting ‘economies’), unequal distribution of power, and political intervention.
Sociology
Keywords: abordaje de sociologí económica; culture; dependencia de camino e institutiones sociales; developing countries; dépendance au chemin parcouru; embeddedness; empirical research; entrepreneurship; imbricación; institutions sociales; kin network; market; path dependency; reciprocity; reciprocity (commerce); social groups; social institutions; social networks; social systems; socioeconomics; utilitarianism

Reading Karl Polanyi for the Twenty-First Century - Bugra, A. (Palgrave Macmillan, 2007)
Using Karl Polanyi's analysis of the separation of politics and the economy, the book argues that the market economy is not a spontaneous process, but a...
Economics; Sociology
Keywords: commodification; financial economics; macroeconomics; market economy; monetary economics

The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Sociology
Keywords: BAUMAN; Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

Neoliberalism or Democracy: Competing Forms of Social Organization in Latin America - Dowd, Jeffrey (Conference Papers – American Sociological Association, 2007)
While political turmoil is not new to Latin America, the tension between neoliberalism and democracy can help explain present-day turmoil. The current political situation in Latin America is the result of a disconnect between the goals of democracy, in particular, between social justice goals, upon which the legitimacy of democratic government rests, and the neoliberal economic policy of the region. Polanyi's concept of the always-embedded economy states that a market economy must be embedded in a market society. Following Polanyi, I argue that markets and democracy require different forms of social organization. Markets and democracy are alternate and competing forms of social organization. The predominance of one often coincides with the restriction of the other. For example, neoliberal governance that maintains market society undermines electoral efficacy. While this may be a general attribute of neoliberalism, previous economic crisis in Latin America increased the need for rhetorical commitment to social justice goals. Latin America's structural position has not changed, however, and international finance and global organizations, like the International Monetary Fund and the World Bank, still constrain Latin American governments. I argue that any resolution to the tension between neoliberalism and democracy must accept the conflicting nature of these two forms of social organization. ..PAT.-Unpublished Manuscript
Sociology
Keywords: Latin America; always embedded economy; democracy; economic policy; embeddedness; free market; free-market; market; neoliberalism; political science; political theory; social justice

Moral Views of Market Society - Fourcade, Marion (Annual Review of Sociology, 2007)
Upon what kind of moral order does capitalism rest? Conversely, does the market give rise to a distinctive set of beliefs, habits, and social bonds? These questions are certainly as old as social science itself. In this review, we evaluate how today's scholarship approaches the relationship between markets and the moral order. We begin with Hirschman's characterization of the three rival views of the market as civilizing, destructive, or feeble in its effects on society. We review recent work at the intersection of sociology, economics, and political economy and show that these views persist both as theories of market society and moral arguments about it. We then argue that a fourth view, which we call moralized markets, has become increasingly prominent in economic sociology. This line of research sees markets as cultural phenomena and moral projects in their own right, and seeks to study the mechanisms and techniques by which such projects are realized in practice.
Sociology
Keywords: capitalism; culture; governmentality; moral markets; moral order; performativity

Globalization, Welfare Reform and the Social Economy: Developing and Alternative Approach to Analyzing Social Welfare Systems in the Post-Industrial Era Special Issue on Globalization: Social Justice & Social Welfare - Gonzales, Vanna (Journal of Sociology and Social Welfare, 2007)
Our understanding of the relationship between globalization and contemporary social welfare systems is heavily influenced by three conventional approaches to studying welfare reform: the political economy, moral economy, and mixed economy approaches.In addition to analyzing the strengths and weaknesses of each of these approaches, a central aim of this article is to introduce the social economy approach as an emergent alternative. Drawing from a growing body of work on institutional innovation within the European third sector, I argue that the social economy approach makes a valuable contribution to understanding the role of welfare networks in recon-figuring globalizations 'impact on the character and quality of social provision so as to better reconcile social efficacy with social justice.
Sociology
Keywords: globalization; social enterprises; social inclusion; social justice; third sector; welfare networks; welfare reform

Embeddedness and the intellectual projects of economic sociology (English) - Krippner, Greta R. [b1] (analytic); Alvarez, Anthony S. [b2] (analytic) (Annu. rev. sociology, 2007)
In this review, we explore how the concept of embeddedness has shaped-and been shaped by-the evolution of the subfield of economic sociology. Although embeddedness is often taken as a conceptual umbrella for a single, if eclectic, approach to the sociological study of the economy, we argue that in fact the concept references two distinct intellectual projects. One project, following from Granovetter's (1985) well-known programmatic statement, attempts to discern the relational bases of social action in economic contexts. Another project, drawing from Polanyi's [1944 (2001), 1957 1977] social theory, concerns the integration of the economy into broader social systems. Critically, these two formulations of embeddedness involve different views of the relationship between the economic and the social. The implication is that the obstacles to theoretical integration in economic sociology, while not insurmountable, are greater than is typically acknowledged. (English)
Sociology
Keywords: GRANOVETTER; Mark; Réseau; action sociale; economic sociology; economic system; economy & society; economy/society; embeddedness; firms; marché; market; markets; network; networks; social action; système économique

India's Double-Movement: Polanyi and the National Alliance of People's Movements - Levien, Michael (Berkeley Journal of Sociology, 2007)
Through an examination of India's National Alliance of People's Movements (NAPM), the largest social movement alliance resisting neoliberal globalization in India, this paper attempts to theoretically reconstruct Polanyi's theory of (t the double movement" for the neoliberal age. Polanyi famously observed that early twentieth century liberal attempts to "dis-embed" the market from social controls created unprecedented social dislocations, leading to widespread protective (< countermovements "to "re-embed" the market within social constraints. I analyze the usefulness and shortcomings of Polanyi's formulation for understanding the current politics of neoliberal globalization. Specifically, I argue that Polanyi failed to explain how a "countermovement" is politically organized and did not develop an adequate theory for the anti-market countermovement he described. Using ethnographic observation ofNAPM's efforts to organize a national alliance against neoliberal globalization, I show how the nature of a "Polanyian" constituency creates previously untheorized obstacles for the effective political organization of a countermovement. These obstacles derive from inherent characteristics of a Polanyian constituency: 1) the economic and social diversity of—and therefore potential antagonism between—its prospective agents, who do not share similar relationships to the means of production, but only the common fact of being negatively affected by the market, and 2) the vastly different ways in which such diverse groups experience market displacements, leadings to a proliferation of single-issue movements whose commonality is hard to perceive and unity difficult to build.
Sociology
Keywords: India; constituents; double movement; globalization; international alliances; neoliberalism; protest movements; resistance movements; social movements

Beyond the boycott: labor rights, human rights, and transnational activism - Seidman, G. (Russell Sage Foundation, 2007)
Sociology
Keywords: business & economics - international; business & economics / business ethics; law / labor & employment; political science / human rights; political science / labor & industrial relations; political science / labour & industrial relations; social science - developing and emerging countries; social science / sociology / general